Ablation of a Single N-Glycosylation Site in Human FSTL 1 Induces Cardiomyocyte Proliferation and Cardiac Regeneration - Ajit Magadum; Neha Singh; Ann Anu Kurian; Mohammad Tofael Kabir Sharkar; Elena Chepurko; Lior Zangi (Elsevier, 2018)
Adult mammalian hearts have a very limited regeneration capacity, due largely to a lack of cardiomyocyte (CM) proliferation. It was recently reported that epicardial, but not myocardial, follistatin-like 1 (Fstl1) activates CM proliferation and cardiac regeneration after myocardial infarction (MI). Furthermore, bacterially synthesized human FSTL 1 (hFSTL1) was found to induce CM proliferation, whereas hFSTL1 synthesized in mammals did not, suggesting that post-translational modifications (e.g., glycosylation) of the hFSTL1 protein affect its regenerative activity. We used modified mRNA (modRNA) technology to investigate the possible role of specific hFSTL1 N-glycosylation sites in the induction, by hFSTL1, of CM proliferation and cardiac regeneration. We found that the mutation of a single site (N180Q) was sufficient and necessary to increase the proliferation of rat neonatal and mouse adult CMs in vitro and after MI in vivo, respectively. A single administration of the modRNA construct encoding the N180Q mutant significantly increased cardiac function, decreased scar size, and increased capillary density 28 days post-MI. Overall, our data suggest that the delivery of N180Q hFSTL1 modRNA to the myocardium can mimic the beneficial effect of epicardial hFSTL1, triggering marked CM proliferation and cardiac regeneration in a mouse MI model. Keywords: cardiomyocytes proilferation, cardiac regeneration, gene therapy